2013
DOI: 10.1371/journal.pone.0076014
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stability Insights into Tumour Suppressor p53 Evolutionary Related Proteins

Abstract: The p53 family of genes and their protein products, namely, p53, p63 and p73, have over one billion years of evolutionary history. Advances in computational biology and genomics are enabling studies of the complexities of the molecular evolution of p53 protein family to decipher the underpinnings of key biological conditions spanning from cancer through to various metabolic and developmental disorders and facilitate the design of personalised medicines. However, a complete understanding of the inherent nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 67 publications
2
24
0
Order By: Relevance
“…The behavior is likely in part due to their DBDs being more stable compared to that of p5318. Consistent with this idea is the lower aggregation tendencies of enhanced stability p53 DBDs.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…The behavior is likely in part due to their DBDs being more stable compared to that of p5318. Consistent with this idea is the lower aggregation tendencies of enhanced stability p53 DBDs.…”
mentioning
confidence: 70%
“…In the present study, long timescale MD simulations were employed in combination with experiments to compare the structural and dynamic properties of p53 family DBDs. The simulations are at least 100 times longer than similar comparative studies1842, providing considerably more time for conformational sampling, with all simulations performed in duplicate to verify consistency in the results.…”
Section: Discussionmentioning
confidence: 93%
“…However, the flexibility of the p53 DBS, and of the L1 loop in particular, has been shown to be essential for DNA binding specificity. Indeed a recent comparison of p53 stability and function in different species showed that the more stable p53 is, the less it interacts (DNA and protein‐protein), and p53‐DNA binding studies showed that p53 scans the DNA before binding specifically to it . First, p53 binds non‐specifically to the DNA, then it drifts along the DNA to find an optimal position on the promoter to which it binds specifically .…”
Section: Discussionmentioning
confidence: 99%
“…Tumor suppressor p53 has been dubbed the "guardian of the genome" due to its central role in cell cycle regulation in response to stress [102,103]. Once p53 is activated by cellular stress signals, it binds DNA to regulate transcription of genes involved in stress response pathways, including cell cycle arrest, senescence, apoptosis, and metabolism [104].…”
Section: P53mentioning
confidence: 99%